2007
DOI: 10.1007/s10610-007-9054-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Aggressive and Violent Behavior: Using Prevention Programs to Study the Role of Peer Dynamics in Maladjustment Problems

Abstract: Two processes in the relationships between children have been associated with adverse developmental outcomes in children, namely, peer rejection and affiliation with deviant peers. In numerous studies, both of these processes have been linked not only to negative outcomes, including aggression, delinquency, violence, but also to school failure or internalizing problems. However, we yet have to understand the exact role of peer dynamics in the development towards maladjustment. Many prevention programs aim at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
8
0
1
Order By: Relevance
“…Intervention groups provide an appropriate context for studying the influence of peer‐group dynamics on children's aggressive behavior. They make it possible to manipulate the context in which the intervention is given and thus to control for effects of peer‐group dynamics (van Lier, Vitaro, & Eisner, 2007).…”
Section: Introduction and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention groups provide an appropriate context for studying the influence of peer‐group dynamics on children's aggressive behavior. They make it possible to manipulate the context in which the intervention is given and thus to control for effects of peer‐group dynamics (van Lier, Vitaro, & Eisner, 2007).…”
Section: Introduction and Theorymentioning
confidence: 99%
“…Ang and Hughes (2001), for example, concluded that negative peer contagion was more effective in homogeneous aggressive groups than in mixed groups or individual treatment, whereas Mager et al (2005) found that in the mixed groups the negative peer contagion was more effective compared with homogeneous aggressive groups. van Lier et al (2007) argued that negative peer contagion is likely to occur in both homogeneous aggressive and mixed intervention groups.…”
Section: Introduction and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…More direct support for the role of competences in psychopathology development comes from results of preventive intervention studies showing that reductions in levels of psychopathology were partially accounted for by improvements in peer relations, such as improved peer acceptance, reduced peer victimization, and reduced affiliation with deviant friends (Bierman et al, 2002; van Lier & Crijnen, 2005; Vitaro, Brendgen, Pagani, Tremblay, & McDuff, 1999; Vuijk, van Lier, Crijnen, & Huizink, 2007; Witvliet, van Lier, Cuijpers, & Koot, 2009). Similarly, in several studies iatrogenic, or unwanted negative effects of intervention were explained by negative peer influences on initially nonaggressive children (Dishion & Dodge, 2005; Dishion, McCord, & Poulin, 1999; Dishion, Poulin, & Burraston, 2001; van Lier, Vitaro, & Eisner, 2007). Other recognition for the entanglement of psychopathology and competences comes from developmental psychopathology, positive psychology, and resilience theory (for an overview, see Masten et al, 2006).…”
mentioning
confidence: 98%
“…Choć w niniejszych badaniach agresję potraktowano jako zmienną niezależną, przyczyniającą się -zgodnie z wieloma koncepcjami -do różnych zachowań antyspołecznych (van Lier, Vitaro, Eisner, 2007), to zarówno agresja, jak i badane cechy wykolejenia są skutkami nieprzystosowania społecznego. Z tego względu przyjęte zmienne jako symptomy mogą dwustronnie na siebie oddziaływać i nie trzeba przestrzegać bezwzględnie zasady przyczynowo-skutkowej w interpretacji danych, gdyż agresja prowadzi do działań antyspołecznych, a samo funkcjonowanie antyspołeczne nie byłoby sfinalizowane, gdyby nie agresja (Underwood, Beron, Rosen, 2011).…”
Section: Wnioskiunclassified